Completing the Loop : Returning Meaningful Learning Analytic Data to Teachers : Final Report. - Kennedy, Gregor; Corrin, Linda; de Barba, Paula (Office for Learning and Teaching, 2016)
The great diversity of the student body in Australian universities is reflected in students ages, cultural and socioeconomic backgrounds, motivations and experiences with technology. University teachers are also increasingly reliant on(and expected to use) a range of technologies to support student learning both on and off campus. In designing and delivering online learning activities to meet diverse student needs, teachers commonly face educational challenges. This project identified common problems faced by teachers and students when learning online, and determine the types of learning analytics teachers would find useful to effectively address these problems. The project developed a web-based analytics tool that will support teachers to more easily interpret learning analytics to help them improve teaching and learning practices. Through an active dissemination program, this project will help to realise the full potential of learning analytics, by providing university teachers with a better understanding of how analytics can be interpreted, applied and actioned.